2008
DOI: 10.1111/j.1445-2197.2008.04713.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Risk Indicator for Necrotizing Fasciitis Score and the Outcomes

Abstract: Background: Laboratory risk indicator for necrotizing fasciitis (LRINEC score) is a simple laboratory tool used to distinguish between necrotizing soft-tissue infections (NSTI) and other soft-tissue infections. A LRINEC score of ‡6 is considered as denoting a high risk of necrotizing fasciitis. A certain LRINEC score might also be associated with mortality and other outcomes of patients with NSTI. Methods: A review of the medical charts of patients was carried out. The study sites were one tertiary academic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 37 publications
5
87
1
10
Order By: Relevance
“…After the application of inclusion and exclusion criteria at the first and second level of screening, 16 articles were included in the final analysis (Kappa 0.72; Fig 1). 9,[16][17][18][19][21][22][23][24][25][26][27][28][29][30][31] The mean MINORS score for comparative studies was 8.6 and 7.0 for non-comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…After the application of inclusion and exclusion criteria at the first and second level of screening, 16 articles were included in the final analysis (Kappa 0.72; Fig 1). 9,[16][17][18][19][21][22][23][24][25][26][27][28][29][30][31] The mean MINORS score for comparative studies was 8.6 and 7.0 for non-comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Su et al 8 reported on the LRINEC score in patients with necrotizing fasciitis. A significant correlation was found between LRINEC X6 and mortality as well as complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the laboratory risk indicator for necrotizing fasciitis (LRINEC) score were calculated on admission in all patients. 7,8 The LRINEC score, which is composed of the following six laboratory tests: glucose level, C-reactive protein level, white blood cell count, sodium level, creatinine level and hemoglobin is a useful adjunct in the initial diagnosis of necrotizing soft tissue infections. 7-9 As Fournier's gangrene is considered a necrotizing infection of the urogenital tract, we used the LRINEC score in our study.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In contrast, our results showed a significantly lower mortality rate of NF in patients with SCI compared with patients without a SCI. Su et al 7 reported that patients with a LRINEC score of X6 have higher rates of mortality and amputation. This was also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum score is 13, a score X6 is suspicious for NF and a score X8 strongly predictive for NF. [7][8][9] Aggressive physiological fluid resuscitation, correction of electrolyte imbalances, extensive operative debridement, antiseptic wound-dressing changes using sterile gauzes and wide-spectrum antibiotic therapy were the therapeutic strategy used in all patients. Radical surgical debridement was required in almost every case before soft tissue closure.…”
Section: Methodsmentioning
confidence: 99%